Predictors of Indonesian National Health Insurance Knowledge: A Cross-Sectional Study Among Public Health Students in Palembang - Ainy, Asmaripa; Pujiyanto, Pujiyanto (Media Kesehatan Masyarakat Indonesia, 2023)
Students, as agents of change, are expected to assist in reaching the success of the Indonesian National Health Insurance/Jaminan Kesehatan Nasional (JKN) program. Therefore, this study aimed to analyze the JKN knowledge among public health students and the associated factors in Palembang City, Indonesia. A cross-sectional online survey was conducted to collect data from 279 students at Universitas Sriwijaya in Palembang City, Indonesia. The analyzed variables included gender, age, marital status, residence, family size, income, study level and period, as well as source of JKN information. Additionally, statistical analysis using binary logistic regression, presenting odds ratio and 95% CI, was conducted to identify the determinants of JKN knowledge with significance set at a p-value <0.05. The results showed that 92.47% of respondents had low JKN knowledge with the following characteristics; female (93.83%), aged >20 years (92.93%), not married (93.75%), living in urban areas (90.24%), having family members >4 people (91.39%), income ≤UMR (93.38%), undergraduate level (93.70%), study period ≤2 years (93.89%), and receiving information from the Social Security Administration Agency for Health/Badan Penyelenggara Jaminan Sosial Kesehatan (BPJSK) (94.32%). The most associated variable with JKN knowledge was residence after being controlled by gender, study period, and information source variables. Specifically, respondents residing in urban areas (aOR = 10.73; 95% CI: 1.32–86.89) showed a higher likelihood of having good JKN knowledge than those in rural areas.